Development of methodology for assessing the effectiveness of tax control types - E. N. Kolesnikova (Вестник университета)
There are two purposes of the study, the results of which are summarised in this article: to systematise modern approaches of assessing the effectiveness of certain tax control forms and to develop proposals for optimising ways to identify the most effective of them. The conclusions made in the article about the change in the determinants that condition the effectiveness of tax control allowed us to justify the need for transformation of approaches to its assessment. The risk-oriented approach proposed by the author to assess the effectiveness of certain tax control types differs from existing views and has not been proposed or considered in the scientific literature before. It focuses on a comparative assessment of the rate of change in the number of taken measures and the results of tax control. Conclusions made on the basis of the implementation of the risk-based approach to assess effectiveness of various tax control forms confirm the conclusions made during the application of quantitative and coefficient methods. However, they are less laborious to obtain results and more visual.